Student Administration Towards the Achievement of the Goals of the School - Salsabila, Putriana Zahra; Kurniawan, Edi (Jurnal Pendidikan Nusantara, 2025)
This study aims to identify important components in school administration that can improve the effectiveness of learning and student management. The method used in this study is qualitative research, which explores data through observation and interviews, where researchers collect data on the implementation of administration, student management, and the interaction between these two aspects. Data was obtained through interviews with principals, teachers, and staff who were still involved in the research. The results show that good and systematic administrative management contributes significantly to the smoothness of the teaching and learning process, as well as the development of student's potential. It was found that a clear and programmed division of administrative tasks in each school can improve efficiency and effectiveness in the implementation of educational activities. In addition, this study also revealed that administration is not only limited to the financial aspect but also includes the continuity of a quality teaching and learning process. Effective and organized administrative services greatly influence the success of education in a school environment. In this increasingly competitive and modern era, schools need to adapt to developments in science and technology and implement innovative administrative practices. Thus, good administrative management will support the achievement of optimal educational goals and the all-round development of students so that schools can function as environments that support effective and sustainable learning.